(3TQM GdQMHjI aj Yde GdaQGFVs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s; (3CHh eMeO YHO GdhgGH Hf Ydj GdbGVj Hf Whb GdKYdHj GdeGdcjs
(3ChdgG (B:s
(3bGd GdTjN GdMeO ddg QH GdYGdejf hGdYGbHI ddeJbjf CeG HYO agPG TQM dWja eNJUQ Ydi GdebOeI GdeSeGI HGdQMHjI s
(3BNQgG (B:s
(3Cbhd (B: (3NJJe cJGHg HGdUdGI HYO MeO Gddg ceG aYdg ai EHJOGA GdcJGH , QLGA HJQc eG HjfgeG hGdYGbHI GdPi dGfHi HYO hGdCeGLO LeY eGLO hbO ced TQa gPG GdTQM s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJH GdeJf HGdMeQI s
(3HBNQgG bUjOI ddMGL MeRI GdcjGdi ai eOM GdQShd s
(3U ai (B27 (3HjJGk s
Keywords: (3Gdabg GdTGaYjs